Butin Attenuates Arthritis in Complete Freund’s Adjuvant-Treated Arthritic Rats: Possibly Mediated by Its Antioxidant and Anti-Inflammatory Actions - Alzarea, Sami I.; Alasmari, Abdullah F.; Alanazi, Abdullah S.; Alzarea, Abdulaziz I.; Alharbi, Metab; Alshammari, Abdulrahman; Kazmi, Imran; Aljoufi, Fakhria A.; Sayyed, Nadeem; Afzal, Muhammad (Frontiers in Pharmacology, 2022)
The present research work was planned to evaluate the antioxidant and anti-inflammatory actions of butin in preventing complete Freund’s adjuvant-induced arthritis in rats. Adult Wistar rats (200–240 g) were segregated equally into four groups: Group I (normal) and Group II complete Freund’s adjuvant (CFA control) were administered orally with 3 ml/kg of 0.5% SCMC (vehicle); Group III and Group IV were test groups and orally administered 25 and 50 mg/kg of butin. These oral treatments were administered for a total of 21 days. In the 21-day treatment schedule, on the first day, animals from group I (normal control) were injected a single dose of normal saline (0.1 ml) intradermally into one of the hind paws, and animals from Group II to IV were injected CFA (0.1 ml) intradermally into one of the hind paws. During the treatment schedule, the volume of the hind paw and body weight were recorded at every 7 days intervals, and animals were scored for severe arthritis on days 17, 19, and 21. On the 22nd day, samples of blood were withdrawn by puncturing the retro-orbital sinus for analysis of RBC, WBC, hemoglobin, ALT, AST, ALP, PGE2, and cytokines. After blood withdrawal, animals were euthanized; the paw was separated by cutting at the ankle joint and used for analysis of oxidative stress and antioxidant parameters, as well as for the histopathological study. Administration of butin to CFA-treated animals significantly attenuated the CFA-induced inflammatory response, oxidative stress, and reversed the histopathological alteration towards normal. According to the findings, butin has anti-inflammatory and anti-arthritic properties in rats with CFA-induced arthritis.